Enhancing Brand Image in the Digital Era: Evidence from Small and Medium-sized Enterprises (SMEs) in Indonesia - Tatik - Suryani; Abu Amar Fauzi; Mochamad Nurhadi (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
This study aims to validate the essential antecedents of brand image enhancement in the digital era, based on a schematic theory. This study involved 400 respondents from four capital cities in Java, Indonesia, which comprise Surabaya, Jakarta, Bandung, and Yogyakarta, based on a quota sampling technique. The findings indicate that the quality of websites and social media sites may have no direct effects on brand image; any effects are transmitted through a serial mediation of brand awareness and E-WOM. Explicitly, the effect of a website’s quality on brand image is fully mediated, while social media’s quality effect on brand image is partially mediated through brand awareness and E-WOM. This study extends the current literature related to SMEs’ brand image. Also, this study offers practical recommendations for several stakeholders interested in empowering SMEs, including the government, entrepreneurship-based universities, and the SMEs themselves, who are all seeking strategies to enhance brand image while utilizing digital platforms such as social media and websites.